Patient Disposition and Clinical Outcome After Referral to a Dedicated TAVI Clinic - Gorecka, Miroslawa; Reddin, Catriona; Madders, Gillian; Monaghan, Laura; Neylon, Antoinette; Sharif, Faisal; Hynes, Brian; Fennelly, Evelyn; McHugh, Fiachra; Martin, Niamh; Mohammed, Khalid; Bijjam, Venu Reddy; et al. (Frontiers in Cardiovascular Medicine, 2020)
Introduction Transcatheter aortic valve implantation (TAVI) is the standard of care for patients with severe symptomatic aortic stenosis (AS) at excessive-, high- and intermediate-surgical risk. A proportion of patients referred for TAVI do not undergo the procedure and proceed with an alternate treatment strategy. There is scarce data describing the final treatment allocation of such patients. Hence, we sought to evaluate the final treatment allocation of patients referred for TAVI in contemporary practice. Methods We performed a single centre prospective observational study, including all patients with AS referred to our institution for TAVI between February 2014 and August 2017. Baseline demographic and clinical data were recorded. Patients were categorized according to treatment allocation: TAVI, surgical aortic valve replacement (SAVR) or optimal medical therapy (OMT). Clinical outcomes were adjudicated according to VARC-2 definitions. All patients were discussed at a dedicated Heart Team meeting. Results Total of 245 patients were referred for TAVI assessment during the study period. Patients with moderate (N=32; 13.1%) and asymptomatic (N=31; 13.1%) AS were excluded. Subsequently, 53.9% (N=132) received TAVI, 12.7% (N=31) were managed with OMT, and 7.3% (N=18) had SAVR. Reasons for OMT included primarily: patient’s preference (N=12; 38.7%); excessive surgical risk (N=4; 12.9%) and severe frailty (N=5; 16.1%). Reasons for surgical referral included low surgical risk (N=11; 61.1%), excessive annulus size (N=5; 27.8%) and aortic root dilatation (N=2; 11.1%). Patients proceeding to SAVR had lower surgical risk than those in either the OMT or TAVI cohorts (P < 0.001). Mean STS score in SAVR group was 2.2±1.3 versus 4.5±2.4 in OMT cohort and 6.1 ± 4.9 in TAVI cohort. Six-month all-cause mortality was 16.7%, 19.4% and 9.3% among those receiving SAVR, OMT and TAVI, respectively. Conclusions Almost half of all patients with severe AS referred to a dedicated TAVI clinic did not receive a TAVI. A considerable proportion of patients were reclassified as moderate AS (13%), were asymptomatic (13%), or intervention was determined to be futile (13%) due to advanced frailty. Early detection and increased awareness of valvular heart disease are required to increase the number of patients that can benefit from TAVI.